Blood glucose monitors: a laboratory and patient assessment. Issue 6211 (9th February 1980) - Webb, D J; Lovesay, J M; Ellis, A; Knight, A H
Abstract : The four blood glucose monitors available in the United Kingdom were compared by asking the opinions of 24 patients who used each monitor for two weeks, by correlating their blood glucose results with those obtained in the laboratory, and by having the monitors examined by an electronics engineer. Of the battery-operated monitors, patients preferred the Hypocount (15) to the Glucochek (9). The mains-operated units were less popular, with little to choose between Eyetone and Reflomat. Under field conditions the blood glucose results obtained with the Glucochek correlated poorly with the standard reference method. In contrast the Hypocount, Eyetone, and Reflomat machines produced good correlations. Poor results with the Glucochek were mainly due to faulty timing systems. The patients' preference for the Hypocount was supported by tests of performance under laboratory conditions and by the electronics engineer's report.